2007
DOI: 10.1007/s10549-007-9668-7
|View full text |Cite
|
Sign up to set email alerts
|

259 Patients with DCIS of the breast applying USC/Van Nuys prognostic index: a retrospective review with long term follow up

Abstract: Although in our series there is not a significant difference in LR rates by the parameter of age, the new USC/VNPI is still a simple and reliable scoring system for therapeutic management of DCIS. We did not find any statistically significant advantage in groups treated with the addition of RT. Obtaining wide surgical margins appears to be the strongest prognostic factor for local recurrence, regardless of other pathological factors or the addition of adjuvant radiation therapy. However, only prospective rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 64 publications
1
76
0
5
Order By: Relevance
“…Studies have suggested that magnification views can aid the prediction of extent of low-grade DCIS (Asjoe et al, 2007;Di Saverio et al, 2008). Our data show that the size discrepancies leading to failed primary BCS occur across all tumour grades and that, numerically, low-grade disease is uncommon (o10% of cases).…”
Section: Discussionmentioning
confidence: 59%
“…Studies have suggested that magnification views can aid the prediction of extent of low-grade DCIS (Asjoe et al, 2007;Di Saverio et al, 2008). Our data show that the size discrepancies leading to failed primary BCS occur across all tumour grades and that, numerically, low-grade disease is uncommon (o10% of cases).…”
Section: Discussionmentioning
confidence: 59%
“…This finding about BCS only, consistent with other studies of women with DCIS or early stage invasive cancer, is a further cause for concern. 21,23,33 Over 25% of our subjects had BCS without RT and although there are a number of clinical factors associated with recurrence or invasive breast cancer after DCIS, [34][35][36] studies have found risks to generally be lower for women treated with BCS and RT opposed to BCS alone. 1,2,16,37,38 Lower screening among women with mastectomy is also problematic as women with DCIS are at higher risk for a second cancer in the opposite breast.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the Van Nuys Prognostic Index (VNPI), combining tumour size, grade and margin width, was used to select 'low-risk' patients not requiring RT (Silverstein et al, 1996), but was widely criticised in two large American and English studies including 222 and 237 patients, respectively (Boland et al, 2003;MacAusland et al, 2007). A recent Italian study (Di Saverio et al, 2008) including 259 patients also used VNPI and concluded in the absence of statistically significant advantage in the CS þ RT vs the CS group. However, the CS þ RT group had several unfavourable factors widely increasing LR risk, such as lesion size 415 mm (67 vs 30%) and excision margins o1 mm (29 vs 4%).…”
Section: Discussionmentioning
confidence: 99%